PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DALAM PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN PAGUBUGAN KULON 04 TAHUN AJARAN 2012/2013 - kurniawan, adi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: THE USE OF COOPERATIVE LEARNING MODEL TYPE ?TAI? INIMPROVING STUDENT MATH LEARNING OUTCOMES IN THE FIFTH GRADERS OF SDN PAGUBUGAN KULON 04 IN THE ACADEMIC YEAR 2012/2013. The purpose of this research is to improve the learning outcomes of mathematics with material fraction arithmetic operations fifth grade elementary school students to use learning model type TAI. This study was conducted in three cycles. Each cycle consists of the planning, execution, observation, and reflection. The subjects were fifth grade elementary school students. Data sources of this study are students, teachers, and observers. Data was collected with tests and non-test techniques. The validity of the data using triangulation techniques and triangulation of data collection sources. Conclusion of this study is the use of TAI cooperative learning model to improve learning outcomes in mathematics fifth grade elementary school students. Keywords: TAI (Team Assisted Individualization), increase math learning outcomes   Abstrak: PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DALAM PENINGKATAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SDN PAGUBUGAN KULON 04 TAHUN AJARAN 2012/2013. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar matematika dengan materi operasi hitung pecahan  siswa kelas V SD dengan penggunaan model pembelajaran tipe TAI. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V SD. Sumber data penelitian ini adalah siswa, guru, dan observer. Teknik pengumpulan data dilakukan dengan teknik tes dan non tes. Validitas data menggunakan teknik triangulasi data dan triangulasi pengumpulan sumber. Simpulan penelitian ini adalah penggunaan model pembelajaran kooperatif tipe TAI dapat meningkatkan hasil belajar matematika pada siswa kelas V SD.   Kata kunci: TAI (Team Assisted Individualization), Peningkatan hasil belajar matematika